Jack Douthett and mathematical music theory. Issue 3 (2nd September 2022) - Yust, Jason
Abstract : Jack Douthett's work over three decades was central to defining an era in mathematical theory. The present special issue attests to his abiding influence over the field, as well as the energy he brought to research in all areas of mathematical music theory through his collaborations, correspondence, and relationships.